2018
DOI: 10.1007/s00248-018-1150-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Microbial Community Structure Along a 7000-Mile Latitudinal Transect from the Mediterranean Sea Across the Atlantic Ocean to the Brazilian Coastal Sea

Abstract: A central goal in marine microecology is to understand the ecological factors shaping spatiotemporal microbial patterns and the underlying processes. We hypothesized that abiotic and/or biotic interactions are probably more important for explaining the distribution patterns of marine bacterioplankton than environmental filtering. In this study, surface seawater samples were collected about 7000 miles from the Mediterranean Sea, transecting the North Atlantic Ocean, to the Brazilian marginal sea. In bacterial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…Dispersal and drift are additional factors that were identified in biogeographic studies (Lindström and Langenheder, 2012;Wilkins et al, 2013). In contrast, the potential influence of the community composition of microorganisms that can interact with heterotrophic microbes has only recently been taken into consideration in this context (Lima-Mendez et al, 2015;Milici et al, 2016;Zhou et al, 2018). The present study reveals that the spatial pattern in the community structure of heterotrophic microbes in surface waters is tightly associated with changes in the diatom assemblages, rather than to geographic distance and environmental conditions.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Dispersal and drift are additional factors that were identified in biogeographic studies (Lindström and Langenheder, 2012;Wilkins et al, 2013). In contrast, the potential influence of the community composition of microorganisms that can interact with heterotrophic microbes has only recently been taken into consideration in this context (Lima-Mendez et al, 2015;Milici et al, 2016;Zhou et al, 2018). The present study reveals that the spatial pattern in the community structure of heterotrophic microbes in surface waters is tightly associated with changes in the diatom assemblages, rather than to geographic distance and environmental conditions.…”
Section: Discussionmentioning
confidence: 66%
“…SA11 and Thalassiosira pseudonana with Croceibacter atlanticus van Tol et al, 2017). These findings in combination with the observed co-occurrence of microbial taxa (Gilbert et al, 2012;Lima-Mendez et al, 2015;Milici et al, 2016;Needham and Fuhrman, 2016;Zhou et al, 2018) raise the question of whether interactions have the potential to drive biogeographic patterns of microbial communities in the aquatic environment.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is now widely accepted that both selective and neutral processes are involved in the assembly of microbial communities, but their relative importance remains intensely debated (Zhou et al ; Stegen et al ; Mo et al ). For example, Zhou et al () found that microeukaryote communities were shaped by environmental selection and biological interactions, which are the main deterministic driving factors governing the distribution patterns of marine plankton at global scales. In contrast, Bahram et al () provide empirical evidence that neutral processes play the dominant role in the distribution of soil microeukaryotes at local levels.…”
mentioning
confidence: 99%